ANALISIS KINERJA APARATUR KECAMATAN DALAM PELAYANAN ADMINISTRASI DI KOTA MEDAN - Irda Fairouz (Universitas Medan Area, 2016)
The problem of service in the field of community administration always colors the relationship between the community and city government. As one of the leading institutions in providing community administration service, subdistrict government in the city of Medan is expected to have the apparatuses who are able to work well in serving the community members. The problem of administration service for the community always occurs when the city government evaluates either its apparatuses or the quality of the provision of administration service for the community. The population of descriptive qualitative study with dominant-less dominant design conducted in the city of Medan was the subdistrict apparatuses and the community members in 21 subdistricts in the city of Medan. The result of this study showed the demand for a qualified community administration service in Medan will be increasing in line with the dynamics of change and population growth in Medan